Gamer [videorecording (DVD)] - Neveldine, Mark; Taylor, Brian; Butler, Gerard, 1969-; Hall, Michael C., 1971-; Valletta, Amber, 1974-; Lerman, Logan, 1992-; Crews, Terry, 1968-; Ludacris (Rapper); Sedgwick, Kyra (Lionsgate, 2010)
Kable is the superstar and cult hero of the ultraviolent Slayers. Kable is controlled by Simon, a young gamer with rock star status who continues to defy all odds by guiding Kable to victory each week. Taken from his family, imprisoned, and forced to fight against his will, the modern-day gladiator must survive long enough to escape the game, free his family, regain his identity, and save mankind from this ruthless technology.